Soil physics - Jury, William A., 1946-; Horton, Robert, 1954- (New York : John Wiley, 2004)
"Soil Physics, Sixth Edition is an essential volume for students and professionals in soil science, natural resource management, forestry, agriculture, hydrology, and civil and environmental engineering."--BOOK JACKET.
1. Soil Solid Phase -- 2. Water Retention in Soil -- 3. Water Movement in Soil -- 4. Water Flow under Natural Conditions -- 5. Soil Thermal Regime -- 6. Soil Aeration -- 7. Chemical Transport in Soil -- App. Methods of Analyzing Spatial Variations of Soil Properties.
Includes bibliographical references (p. 337-359) and index.
Keywords: Soil physics